White discourse in post-independence Zimbabwean literature - McClelland, Roderick William (Department of English Language and Literature, 2016)
Literally hundreds of novels were written by white Rhodesians during the U.D.I. era of the 1960s and 1970s. Since Independence, however, not much more than a handful of literary texts have been produced by whites in Zimbabwe. This dissertation, therefore, involves an interrogation of both white discourse and the (reduced) space for white discourse in postcolonial Zimbabwean society. In addition to the displaced moral space, and the removal of the economic and political power base, there has been an appropriation of control over the material means of production of any discourse and white discourse, which has become accustomed to its position of superiority due to its dominance and dominating tendencies, has struggled to come to terms with its new, non-hegemonic 'space'. In an attempt to come to some understanding of the literary silence and marginalisation of white discourse in post-independence Zimbabwe there has to be some understanding of the voice that was formed during the British South Africa Company's administration and which reached a crescendo of authoritarian self-assertion at the declaration of unilateral independence. Vital to this discussion (in Part I) is an uncovering of the myths that were intrinsic to white discourse in the way that they were created as justification for settlement and to propagandise the aggressive defence of that space that was forged in an alien landscape. These myths have not been easily cast aside and, hence, have made it so difficult for white discourse to adapt to post-colonial society. Most Rhodesian novels were extremely partisan and promulgated these myths. Part II, discusses ex post facto novels about the war (from the white perspective) to investigate whether white discourse is recognising the lies that make up so much of its belief system. This investigation of this particular perspective of the war, then, will help to define at what stage white Zimbabweans are at in the development of a national culture. Part III takes this discussion of acculturation and national unity further. Furthermore, through the discussion of a number of novels in this chapter, it is argued that white discourse is struggling to come to terms with its non-hegemonic position and is continuing to attempt to assert its control. The 'space' available to the early settlers' discourse for appropriation, however, has been removed and, in the reduced space available to white discourse, one continued area of possible control is that of conservation.